Mae Ya Nang: Adolescents’ Perceptions and Safe Driving Behaviors: Mae Ya Nang: Adolescents’ Perceptions and Safe Driving Behaviors - Nilsang, Jiranun; Yanthong, Thanad (RATANABUTH JOURNAL, 2026)
This research aimed to: 1) study the history, traditions, beliefs, and rituals related to Mae Yanang, and 2) examine beliefs about Mae Yanang in relation to perception formation and driving behavior. The informants were selected through purposive sampling and consisted of three groups: 1) key informants, who possessed in-depth knowledge about the history, beliefs, and cultural perspectives; 2) practitioner informants, who provided information on beliefs about Mae Yanang in relation to perception formation and driving behavior; and 3) general informants, including private car drivers who had never attended a driving school, regular motorcycle riders, and general road users. This study employed a qualitative cultural research approach. Data collection instruments included surveys, interviews, observations, focus group discussions, and workshops. The findings revealed that: 1) Mae Yanang continued to play a role as a cultural mechanism that reinforced awareness and safety attitudes rather than directly determining behavior. Such beliefs should be integrated with reason, laws, training, and modern learning to create a sustainable road safety culture. 2) Belief in Mae Yanang functioned as a cultural and psychological mechanism linking travel with the concept of safety. It reflected the adaptation of Thai culture from the past to the present by promoting mindfulness, discipline, and responsibility rather than directly controlling behavior, and it could be integrated with modern learning to foster a culture of safety.